Distributed generalized cyclic delay diversity for cooperative OFDM systems - Chen, Harry Z. B.; Schober, Robert; Lampe, Lutz (IEEE Vehicular Technology Conference, 2008)
In this paper, we introduce distributed generalized cyclic delay diversity (DGCDD) for cooperative signaling in orthogonal frequency division multiplexing (OFDM) wireless relay networks. We assume that the set of cooperating nodes is a priori unknown and assign each node in the network a fixed cyclic filter (CF). Assuming bit-interleaved coded modulation (BICM) for forward error correction, we derive an optimization criterion for the CFs and show that DGCDD can exploit the full diversity of the wireless channel. A numerical method for CF design is provided and compared with randomly generated Alters. Simulation results confirm the excellent performance of the proposed scheme and show that the performance loss of DGCDD compared to GCDD with co-located antennas is small for sufficiently long CFs. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03